Custom made ocular prosthesis for acquired eye defect:Adefinitive option of rehabilitation - Farook, Taseef Hasan; Rahman, Ahmed Mushfiqur; Islam Nizami, Md Minhaz Ul; Amin, Mehedi; Jamayet, Nafij Bin; Alam, Mohammad Khursheed (Bangladesh Journal of Medical Science, 2019)
Objective:This case report describes the rehabilitation process of a case of acquired eye defect with patient specific or custom made ocular prosthesis for a patient who had her left eye surgically enucleated as a treatment step for retinoblastoma. Method: After primary evaluations, an intraorbital impression was taken while reproducing natural eye movements to ensure accuracy of the impression. The impression was cast and a transparent acrylic conformer was made from the mould in the cast. The conformer was adjusted as required and Iris position determined. The conformer was then used to cast the final custom ocular prosthesis. The patient was then instructed on its usage and maintenance. Result: A custom made ocular prosthesis was provided to the patient and it was to her satisfaction. Conclusion: Custom made ocular prosthesis is highly recommended in rehabilitation of facial defects of a co-operative patient as it does not have most of the limitations which a stock ocular prosthesis does. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.823-826